1985
DOI: 10.1111/j.1528-1157.1985.tb05713.x
|View full text |Cite
|
Sign up to set email alerts
|

Aminophylline and CGS 8216 Reverse the Protective Action of Diazepam Against Electroconvulsions in Mice

Abstract: Aminophylline (50 and 100 mg/kg) and CGS 8216 (20 and 40 mg/kg) decreased the anticonvulsant potency of diazepam (5 and 10 mg/kg) against electroshock-induced seizures. It should be emphasized that aminophylline moderately affected the protective action of the benzodiazepine at a dose of 5 mg/kg, whereas it was equipotent with CGS 8216 with regard to diazepam at a dose of 10 mg/kg. Consequently, participation of a purinergic component in the anticonvulsant action of diazepam is suggested. On the other hand, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Therefore, it might be suggested that adenosine-mediated events are not involved in the mechanisms of the protective action of carbamazepine, diazepam, phenobarbital, and valproate against electroconvulsions. In this context, aminophylline-and caffeine-induced impairment of the anticonvulsant effects of these antiepileptic drugs (Czuczwar et al, 1985(Czuczwar et al, , 1986(Czuczwar et al, , 1987b would seem independent of adenosine receptor blockade as well. Adenosine, to some extent might participate in the mechanism of anticonvulsant activity of diphenylhydantoin and the additional evidence was provided by our earlier results on the reversal of the protective activity of some antiepileptics by a number of methylxanthine derivatives (Czuczwar etal., 1990 a).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, it might be suggested that adenosine-mediated events are not involved in the mechanisms of the protective action of carbamazepine, diazepam, phenobarbital, and valproate against electroconvulsions. In this context, aminophylline-and caffeine-induced impairment of the anticonvulsant effects of these antiepileptic drugs (Czuczwar et al, 1985(Czuczwar et al, , 1986(Czuczwar et al, , 1987b would seem independent of adenosine receptor blockade as well. Adenosine, to some extent might participate in the mechanism of anticonvulsant activity of diphenylhydantoin and the additional evidence was provided by our earlier results on the reversal of the protective activity of some antiepileptics by a number of methylxanthine derivatives (Czuczwar etal., 1990 a).…”
Section: Discussionmentioning
confidence: 97%
“…Aminophylline (up to 100 mg/kg; 0.476 mmol of anhydrous theophylline/kg) remained also without effect on the threshold, the result being obtained elsewhere (Czuczwar et al, 1985).…”
Section: Effect Of 8-(p-sulfophenyl) Theophylline On the Threshold Fomentioning
confidence: 87%
“…There is well documented evidence that strychnine and aminophylline impaired the anticonvulsant potency of conventional antiepileptic drugs against maximal electroshock-induced seizures in mice (Czuczwar et al, 1985(Czuczwar et al, , 1986(Czuczwar et al, , 1987a(Czuczwar et al, , b, 1991. Further, any pharmacokinetic interactions, which could account for these effects, were not probable (Czuczwar et al, 1989(Czuczwar et al, , 1991.…”
Section: Discussionmentioning
confidence: 97%
“…However, it is not clear to what extent these mechanisms participate in the induction of seizure activity and whether there are any further mechanisms responsible for this phenomenon. Aminophylline was also reported to reverse the anticonvulsant action of various antiepileptic drugs against seizures induced by maximal electroshock or that of phenobarbital against amygdala-kindled seizures in rats (Czuczwar et al, 1985(Czuczwar et al, , 1986(Czuczwar et al, , 1987a(Czuczwar et al, ,b, 1989. (Aebischer et al, 1989) and 1-(4-aminophenyl)-4-methyl-7,8-methylenedioxy-5H-2,3-benzodiazepine (GYKI 52466), a non-competitive a-amino-3-hydroxy-5-methyl-4-isoxazolepropionate/kainate (AMPA/KA) antagonist (Tarnawa et al, 1990;Donevan and Rogawski, 1993), have been recently tested in various models of experimental epilepsy (Smith et al, 1991;Rogawski, 1992;Tutka et al, 1992;Yamaguchi et al, 1993;Czuczwar et al, 1994).…”
Section: Introductionmentioning
confidence: 99%